Enhancing MSME Performance: The Mediating Role of Job Satisfaction between ICT Utilization and Work Discipline - Dewi, Wulan Riska; Basrowi; Khaeruman (LP2M IBK Nitro, 2025)
This study aims to analyze the effect of Information and Communication Technology (ICT) utilization and work discipline on employee performance, with job satisfaction as a mediating variable in Micro, Small, and Medium Enterprises (MSMEs). The utilization of ICT plays an important role in increasing work efficiency and effectiveness, while work discipline reflects the responsibility and consistency of employees in carrying out their duties. This study uses a quantitative approach with a survey method on MSME employees in Serang City. The study population was 752 employees, and 190 respondents were taken as the research sample. The sampling technique used Random Sampling with a Proportional Random Sampling approach so that each sub-district could be represented. Data analysis was carried out using the Partial Least Square – Structural Equation Modeling (PLS-SEM) method using Stratified SmartPLS software. The results of the study indicate that the utilization of ICT and work discipline have a positive and significant effect on employee performance. In addition, job satisfaction is proven to mediate the relationship between ICT and work discipline on employee performance. These results confirm that mastery of ICT and the implementation of good work discipline can increase job satisfaction, which ultimately has a positive impact on the performance of MSME employees..